Strain, Soil-Type, Irrigation Regimen, and Poultry Litter Influence Salmonella Survival and Die-off in Agricultural Soils - Bardsley, Cameron A.; Weller, Daniel L.; Ingram, David T.; Chen, Yuhuan; Oryang, David; Rideout, Steven L.; Strawn, Laura K. (Frontiers in Microbiology, 2021)
The use of untreated biological soil amendments of animal origin (BSAAO) have been identified as one potential mechanism for the dissemination and persistence of Salmonella in the produce growing environment. Data on factors influencing Salmonella concentration in amended soils are therefore needed. The objectives here were to (i) compare die-off between 12 Salmonella strains following inoculation in amended soil, and (ii) characterize any significant effects associated with soil-type, irrigation regime, and amendment on Salmonella survival and die-off. Three greenhouse trials were performed using a randomized complete block design. Each strain (~4 log CFU/g) was homogenized with amended or non-amended sandy- or clay-loam soil. Salmonella levels were enumerated in 25g samples 0, 0.167 (4h), 1, 2, 4, 7, 10, 14, 21, 28, 56, 84, 112, 168, 210, 252, and 336 d post-inoculation, or until two consecutive samples were enrichment negative. Regression analysis was performed between strain, soil-type, irrigation, and (i) time to last detect (survival) and (ii) concentration at each time-point (die-off rate). Similar effects of strain, irrigation, soil-type and amendment were determined using the survival and die-off models. Strain explained up to 18% of the variance in survival, and up to 19% of variance in die-off rate. On average Salmonella survived for 129 d in amended soils, however Salmonella survived, on average, 30 days longer in clay-loam soils than sandy-loam soils [95% Confidence Interval (CI)=-45, -15), with survival time ranging from 84 to 210 days for the individual strains during daily irrigation. When strain-specific associations were investigated using regression trees, S. Javiana and S. Saintpaul were found to survive longer in sandy-loam soil, whereas most of the other strains survived longer in clay-loam soil. Salmonella also survived, on average,128 d longer when irrigated weekly, compared to daily (CI=101, 154), and 89 d longer in amended soils, then non-amended soils (CI=61, 116). Overall, this study provides insight into Salmonella survival following contamination of field soils by BSAAO. Specifically, Salmonella survival may be strain-specific as affected by both soil characteristics and management practices. These data can assist in risk assessment and strain selection for use in challenge and validation studies.